2010
DOI: 10.1111/j.1365-2141.2010.08185.x
|View full text |Cite
|
Sign up to set email alerts
|

MDM4 (MDMX) is overexpressed in chronic lymphocytic leukaemia (CLL) and marks a subset of p53wild‐type CLL with a poor cytotoxic response to Nutlin‐3

Abstract: Cutaneous manifestations of cryoglobulinemia: clinical and histopathologic study of seventy-two patients. Journal of the American Academy of Dermatology, 25, 21-27. Kern, J., Untergasser, G., Zenzmaier, C., Sarg, B., Gastl, G., Gunsilius, E. & Steurer, M. (2009) Although about one-third of patients with B-cell chronic lymphocytic leukaemia (CLL) never require treatment, in other patients the disease progresses at a variable rate and requires treatment regimens by alkylating agents, purine analogs, monoclona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…First, this further supports the notion that MdmX depletion is a critical mechanism to inactivate oncogenic Mdm2–MdmX E3 complex and accordingly activates p53 signaling in cells (39), because MdmX stimulates Mdm2-mediated p53 monoubiquitination and is required for p53 polyubiquitination (36, 38). Second, FL118 can be used as an MdmX-depleting agent in MdmX-targeting therapies for a subgroup of patients with cancer (i.e., a type of personalized medicine) such as in chronic lymphocytic leukemia (49) and melanomas (50), in which MdmX overexpression confers treatment resistance. Our studies provided evidence that FL118 inhibits growth of MdmX-overexpressing cells better than non–MdmX-overexpressing cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…First, this further supports the notion that MdmX depletion is a critical mechanism to inactivate oncogenic Mdm2–MdmX E3 complex and accordingly activates p53 signaling in cells (39), because MdmX stimulates Mdm2-mediated p53 monoubiquitination and is required for p53 polyubiquitination (36, 38). Second, FL118 can be used as an MdmX-depleting agent in MdmX-targeting therapies for a subgroup of patients with cancer (i.e., a type of personalized medicine) such as in chronic lymphocytic leukemia (49) and melanomas (50), in which MdmX overexpression confers treatment resistance. Our studies provided evidence that FL118 inhibits growth of MdmX-overexpressing cells better than non–MdmX-overexpressing cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although trisomy 12 is the most common cytogenetic change in CLL, trisomy 12 has not been associated with overexpression of MDM2. MDMX overexpression has also been reported in CLL [19]. ATM, which is activated in response to DNA double-strand breaks, synchronizes DNA repair with the induction of p53-dependent apoptosis.…”
Section: P53 Regulatory Abnormalities In Leukemiamentioning
confidence: 99%
“…It has been reported that increased expression of MDM2 predicts higher cell sensitivity to MDM2 inhibitors [30, 58]. On the other hand, cells with MDMX overexpression or TP53 mutations generally show poor inhibitor sensitivity [19, 2935]. By interrogating high-throughput cell line and patient-derived tumor xenograft sensitivity data with genomic profiling data, a gene expression signature consisting of 13 p53 transcriptional target genes has been identified that predicts sensitivity to the MDM2 inhibitor NVP-CGM097 [72].…”
Section: Predictive Biomarkers For Response To Mdm2 Inhibitorsmentioning
confidence: 99%
“…104 Interestingly, MDM4 overexpression has been associated with lack of response to the MDM2 antagonist nutlin in chronic lymphoma cells in vitro. 105 In a recent phase I study exploring an MDM2 antagonist administered as monotherapy to patients with liposarcomas, for which most were amplified for MDM2, one patient achieved a partial tumour response while several had stable disease, 106 advocating further studies in concert with chemotherapy.…”
Section: Tp53 Analogues Tp63 and Tp73mentioning
confidence: 99%